2003
DOI: 10.1093/cercor/13.4.340
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI Studies of Human Visual Motion Perception: Texture, Luminance, Attention and After-effects

Abstract: Motion of an object is thought to be perceived independently of the object's surface properties. However, theoretical, neuropsychological and psychophysical observations have suggested that motion of textures, called 'second-order motion', may be processed by a separate system from luminance-based, or 'first-order', motion. Functional magnetic resonance imaging (fMRI) responses during passive viewing, attentional modulation and post-adaptation motion after-effects (MAE) of these stimuli were measured in seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 73 publications
9
62
0
4
Order By: Relevance
“…The results presented here demonstrate that not only is behaviorally relevant information concerning stimulus speed encoded by activity in human area V5/MTϩ, but that it is also encoded by activity within area V3A. The fact that we can induce deficits in perception by applying rTMS to area V3A indicates that information about speed is available at this level and would appear to cement the prominent status of V3A in the cortical network that exists for the processing of motion in the human brain (Tootell et al, 1997;Smith et al, 1998;Seiffert et al, 2003;Liu and Wandell, 2005).…”
Section: Cortical Areas Involved In Speed Perceptionmentioning
confidence: 55%
See 1 more Smart Citation
“…The results presented here demonstrate that not only is behaviorally relevant information concerning stimulus speed encoded by activity in human area V5/MTϩ, but that it is also encoded by activity within area V3A. The fact that we can induce deficits in perception by applying rTMS to area V3A indicates that information about speed is available at this level and would appear to cement the prominent status of V3A in the cortical network that exists for the processing of motion in the human brain (Tootell et al, 1997;Smith et al, 1998;Seiffert et al, 2003;Liu and Wandell, 2005).…”
Section: Cortical Areas Involved In Speed Perceptionmentioning
confidence: 55%
“…Without doubt, the most intensively studied of these is area V5/MTϩ, whereas, by comparison, other areas of the brain that respond to motion have received much less interest. One such area, V3A, has been found to be second only to V5/ MTϩ in terms of its sensitivity to motion (Tootell et al, 1997;Smith et al, 1998;Seiffert et al, 2003), but little is known about the exact nature of its contribution to motion perception. Similarly, the study of the neural mechanisms that underpin the perception of speed has also tended to focus on the role played by V5/MT.…”
Section: Introductionmentioning
confidence: 99%
“…Another challenge to the hypothesis that motion-processing deficits in ASD are specific to secondorder motion is presented by the finding that neural responses to first-and second-order motion do not differ as much as originally had been assumed (Seiffert, Somers, Dale, & Tootell, 2003). Dakin and Frith (2005) have argued that visual attention provides a better explanation of the findings by Bertone et al (2003), since the visual perception of second-order motion shows a greater dependence on attentional processes than does the perception of first-order motion (Cavanagh, 1992).…”
Section: Interpreting Apparently Divergent Resultsmentioning
confidence: 99%
“…Using this technique they found evidence for separate populations of cells sensitive to first-order and second-order motion in several visual areas including V3A, MT and MST (technical issues may have prevented adequate examination of responses in V1). Nishida et al [34] and Seiffert et al [35] had previously found fMRI responses to both first-order and second-order motion in a number of visual areas including V1, V2, V3, VP, V3A, V4v, and MT.…”
Section: Human Brain Imagingmentioning
confidence: 99%
“…The essential principle of population coding in the MAE is still universally accepted, but discoveries made possible with the introduction of new experimental techniques indicate that major changes to theoretical explanations of the MAE are required. These discoveries include work in human psychophysics [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], primate physiology [24][25][26][27], human neuroimaging [28][29][30][31][32][33][34][35][36][37], human electrophysiology (Visual Evoked Potentials -VEPs) [38][39][40][41][42] and transcranial stimulation [43][44][45]. Results indicate that the MAE is an amalgam of neural adaptation at several visual cortical sites.…”
Section: Introductionmentioning
confidence: 99%